RETRACTED: Mfn2 Overexpression Attenuates Cardio-Cerebrovascular Ischemia–Reperfusion Injury Through Mitochondrial Fusion and Activation of the AMPK/Sirt3 Signaling - Liu, Min; Li, Xiaoyang; Huang, Dezhi (Frontiers in Cell and Developmental Biology, 2020)
Mitochondria are potential targets for the treatment of cardio-cerebrovascular ischemia-reperfusion (I/R) injury. However, the role of the mitofusin 2 (Mfn2) protein in regulating mitochondrial fusion and cell survival has not been investigated. In the present study, an adenovirus-mediated Mfn2 overexpression assay was performed to understand the effects of Mfn2 on mitochondrial function and cell damage during cardio-cerebrovascular I/R injury. After exposure to I/R injury in vitro, the transcription and expression of Mfn2 were significantly downregulated, which correlated with decreased cell viability and increased apoptosis. By contrast, overexpression of Mfn2 significantly repressed I/R-mediated cell death through modulation of glucose metabolism and oxidative stress. Furthermore, Mfn2 overexpression improved mitochondrial fusion in cells, an effect that was followed by increased mitochondrial membrane potential, improved mitophagy, and inhibition of mitochondria-mediated apoptosis. Our data also demonstrated that Mfn2 overexpression was associated with activation of the AMPK/Sirt3 signaling pathway. Inhibition of the AMPK/Sirt3 pathway abolished the protective effects of Mfn2 on I/R-induced cell injury arising from mitochondrial damage. Our results indicate that Mfn2 protects against cardio-cerebrovascular I/R injury by augmenting mitochondrial fusion and activating the AMPK/Sirt3 signaling pathway.